Implementation of the Policy of the Office of Food Crops, Horticulture, Plantations, and Food Security in Achieving Food Self-Sufficiency in Cianjur Regency, West Java Province (International Forum of Researchers and Lecturers, 2025)
Food self-sufficiency is essential for human survival. Achieving food self-sufficiency significantly impacts distribution, including equitable distribution of food across regions, time periods, and income groups, including affordability of food prices at various local, regional, and national levels. This situation is ironic considering that meeting food needs is faced with a number of challenges, including the recruitment of young people to work in the agricultural sector, with less competitive incentives, and the continued decline in land availability as the population increases. This research utilizes Jones's (1994: 296) theory on policy implementation. The method used is descriptive with a qualitative approach that systematically describes facts, object characteristics, and subjects from empirical observations. Data collection techniques include in-depth interviews, observations, and documentation studies to examine in-depth and account for the variety of policy implementation issues of the Food Crops, Horticulture, and Plantation Service in achieving food self- sufficiency in Cianjur Regency, West Java Province. The results show that achieving food self-sufficiency involves implementing policies through its pillars, including: (i) The program's implementation organization has not been effective in managing resources to support its implementation. (ii) the interpretation of socialization has not been effective in meeting the desired targets. (iii) the application of direct support from activity implementers at all levels, from the village, sub-district, and district levels, has not been effective. This is because field coordinators and field officers have not carried out their duties properly and there is still a lack of supervision.